Highly durable and conductive poly(arylene piperidine) with a long heterocyclic ammonium side-chain for hydroxide exchange membranes. (20th September 2019) - Jin, Cuihong; Zhang, Shuai; Cong, Yuanyuan; Zhu, Xiuling
Abstract: Recently, the preparation of hydroxide exchange membranes (HEMs) without ether bonds have attracted much attention because of their high chemical stability. Hence, ether-bond free, highly durable, and conductive poly(arylene piperidine)s (PAPips) tethered with heterocyclic ammonium via hexyl spacer chains were prepared successfully for HEMs via a facile synthetic procedure. The effect of the cationic groups (quaternary ammonium, piperidinium, and morpholinium) on the properties of the corresponding PAPip-based HEMs, including the morphology, hydroxide conductivity, and alkaline and chemical stability were systematically investigated. The as-designed PAPip-based membranes exhibited excellent overall performance. The membranes attached with piperidinium (IEC = 1.64 mmol g −1 ) exhibited a hydroxide conductivity of 0.082 S cm −1 at 80 °C and exhibited significant alkaline stability which maintained 80.1% of its conductivity after immersion in 1 M NaOH at 80 °C for 1500 h. The as-prepared membrane also presented a peak power density of 76 mW cm −2 at 80 °C in a H2 /O2 HEMFC. The resulting HEMs also showed excellent mechanical properties, thermal stability, and well-defined phase separation. Graphical abstract: Image 1 Highlights: Ether-bond free FPAPip membranes were successfully prepared. FPAPip membranes show superior alkaline stability. FPAPip membranes exhibit high hydroxide conductivity. FPAPip membranes show excellent oxidative stability.